Falling Snow Radiative Effects Enhance the Global Warming Response of the Tropical Pacific Atmosphere. Issue 18 (17th September 2018) - Chen, Chao‐An; Li, J.‐L. F.; Richardson, Mark; Lee, Wei‐Liang; Fetzer, Eric; Stephens, G.; Hsu, Huang‐Hsiung; Wang, Yi‐Hui; Yu, Jia‐Yuh
Abstract: Most models from the Coupled Model Intercomparison Project phase 5 (CMIP5) do not include the radiative effects of falling snow. This has been shown to bias simulations of radiation and circulation in the Pacific present‐day mean state. Here we explore how precipitating ice radiative effects contribute to simulated Pacific climate change via a pair of sensitivity experiments with and without snow radiative effects (SnowOn/SnowOff) using 1pctCO2 simulations of the Community Earth System Model version 1 (CESM1) climate model, in which atmospheric CO2 increases at 1% per year for 140 years. In addition, we compare our results with the CMIP5 ensemble mean. The initial climate state of each 1pctCO2 run shows similar patterns to present‐day simulations. Under global warming, the regions of convective activity tend to intensify and shift eastward. These changes are stronger in the SnowOn simulation, which also displays a stronger zonal gradient of sea surface temperature warming relative to SnowOff. The changes in convective activity and the associated precipitation are particularly notable: with reduced precipitation around the maritime continent, and an approximate doubling of the precipitation increase over parts of the western Pacific in SnowOn. CESM1 SnowOff patterns of change are similar to those in CMIP5 models that exclude snow radiative effects, hinting that future warming‐driven changes in precipitation and circulation over the Pacific might be stronger than those simulated by most CMIP5 models. Key Points: Radiative effect associated with precipitating ice (snow) is not considered in most GCMs The impacts of snow radiative effects under global warming are investigated in a 1pctCO2 simulation Changes in tropical Pacific climate are enhanced when the snow radiative effect is considered